PENERAPAN MODEL ASSURE DENGAN MENGGUNAKAN MEDIA POWER POINT BERBASIS ANIMASI DAN VIDEO DALAM PEMBELAJARAN FIQIH - SRI RAHAYU DINDA YANI; DINA NOVITA AMALIYAH (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
The process of studying Fiqh in schools shows that there are still many students who get grades below the specified standard. This happens because there is still a lack of teachers in using learning media in the learning process so that student learning outcomes are low. Learning media is a tool in the teaching and learning process. Learning media is applied to increase students in learning activities, with teachers applying interesting media, students will be enthusiastic in participating in learning and student learning outcomes will increase. The purpose of this research for this research is the application of animation-based power point media to improve student learning outcomes class and achieving learning designs that are in accordance with planning, effective and efficient learning and also make teachers more creative in using more interesting learning media. This research was conducted at SD Muhammadiyah 8 Surabaya. The class used as the research setting is class V. The subject used for the research object is the subject of Fiqh. This study uses a qualitative approach. The data collection techniques are interviews, observation, documentation, and questionnaires. The results showed that the use of the Assure model using animation and video-based power point media can add variety to learning and improve learning outcomes and student learning motivation, by analyzing student characteristics, learning styles, selecting appropriate methods, media and teaching materials, and involving students are active in learning.